New Evidence on the Missing Resource-Performance Link in Education - Ludger Wößmann (Kiel Institute of World Economics (IfW), 2001)
New evidence confirms the conclusion of former surveys that the link between school resources and student performance is generally missing in educational production. While the conventional within-country cross-section evidence remains controversial, recent contributions which control for potential resource endogeneity suggest that returns to resource usage in education are decreasing. Resources may render positive effects at very low endowment levels prevailing in many developing countries, but their effect is weak to non-existent in advanced countries. The missing resource-performance link in education also shows up in international cross-section evidence and in within-country time-series evidence.
Keywords: I2; 330; education production functions; determinants of student performance; resource effects; Bildungsökonomik; Produktionsfunktion; Bildungsniveau; Bildungsinvestition; Bildungsforschung; Welt